2017
DOI: 10.4103/ijem.ijem_397_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid peroxidase antibody and pregnancy outcome in euthyroid autoimmune positive pregnant women from a tertiary care center in Haryana

Abstract: Objective:To study the prevalence of thyroid peroxidase autoantibody in euthyroid pregnant women and to evaluate the association between thyroid peroxidase autoantibody and pregnancy outcomes.Materials and Methods:One thousand thirty consecutive pregnant women attending the antenatal clinic over a period of 1 year and were carrying a healthy singleton uncomplicated intrauterine pregnancy and consuming iodized salt were recruited for the study. Outcomes of the pregnancy was compared between TPO antibody positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…The relevance between the abnormal elevation of TPOAbs and offspring autism has also been reported by researcher [ 88 ]. The abnormal elevation of TPOAbs has not been reported as a causal factor of parity, period of gestation, or body weight [ 71 ].…”
Section: Clinical Significance Of Trabs Tpoabs and Tgabsmentioning
confidence: 99%
“…The relevance between the abnormal elevation of TPOAbs and offspring autism has also been reported by researcher [ 88 ]. The abnormal elevation of TPOAbs has not been reported as a causal factor of parity, period of gestation, or body weight [ 71 ].…”
Section: Clinical Significance Of Trabs Tpoabs and Tgabsmentioning
confidence: 99%
“…Three studies found an association between thyroid autoimmunity and miscarriage (34)(35)(36). In a case-control study of 150 pregnant, euthyroid women with TPOAbs and 150 pregnant, euthyroid women without TPOAbs, Rajput et al reported a significant increase in miscarriage in women with TPOAbs compared to those without, 12% (18/150) vs. 3.3% (5/150), respectively, P = 0.004 (34).…”
Section: A) Autoimmunity and Miscarriage (Question 16) "Is There An Amentioning
confidence: 99%
“…"Is there an association between thyroid autoantibody positivity and premature delivery?" Four studies examined the association between thyroid autoimmunity and preterm delivery (34,(38)(39)(40), three of which were positive (34,38,40). In the study by Rajput et al TPOAb positive women had a significant increase in preterm delivery compared to TPOAb negative women, 14% (21/150) vs. 3.3% (5/150), respectively, P = 0.001 (34).…”
Section: C) Autoimmunity and Preterm Delivery (Question 19)mentioning
confidence: 99%
See 2 more Smart Citations